Assessment of Pedestrian Sidewalk Utilization (Case Study of Jalan Gajah Mada) - Dzulqolbirrohim, Muhammad Fadhil; Mayuni, Siti; Octaviana, Yanti (Jurnal Teknik Sipil, 2025)
The rapid economic growth in major Indonesian cities has led to increased movement of people and goods, particularly in commercial centers, office districts, schools, places of worship, and other urban areas. To accommodate pedestrians while ensuring smooth traffic flow, the government is responsible for providing adequate sidewalk infrastructure. However, in practice, sidewalks often fail to function as intended. In response, the Pontianak City Government plans to expand and enhance sidewalk networks to create a more pedestrian-friendly urban environment. This study applies the Guttman Scale method in accordance with Regulation of the Minister of Public Works No. 03/PRT/M/2014 and Guideline 07/P/BM/2023 to assess sidewalk conditions. Additionally, pedestrian satisfaction is evaluated through interviews using the Likert Scale method. The assessment of existing sidewalk conditions, based on technical guidelines, produced the following results: safety (56.25%), comfort (100%), accessibility (37.50%), aesthetics (87.50%), connectivity (33.33%), and supporting facilities (15%). Meanwhile, pedestrian satisfaction ratings were accessibility (82.83%), climate and natural resilience (85.56%), air quality/odor (86.67%), cleanliness (69.44%), aesthetics (80.83%), safety (81.67%), supporting facilities (76.43%), and obstacles (71.67%). These findings highlight key areas for improvement and underscore the need for comprehensive urban planning strategies to enhance pedestrian infrastructure and overall sidewalk usability in Pontianak.